Keterkaitan Tingkat Efektifitas Metode Fitoremediasi Terhadap Tingkat Pertumbuhan Media Eceng Gondok Pada Limbah Cair C6+ - Safitri, Dewi; Patandjengi, Baharuddin; Syahrul, Muhammad; Fahruddin; Budimawan; Demmallino, Emmal Basham (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2024)
Liquid waste of Cr6+ is often produced by nickel ore mining companies, one of which is CV. Unaha Bakti Persada has a Cr6+ concentration of 0.78 ppm which has not yet reached the 0.1 ppm quality standard, so it is necessary to treat Cr6+ waste using an in vitro phytoremediation technique for water hyacinth media of E. azurea and E. crassipes. The purpose of this study was to determine the effectiveness of phytoremediation method, the level of damage to water hyacinth and the rate of growth of the water hyacinth plant. The study used an in vitro phytoremediation method for water hyacinth media E. crassipes and E. azurea for 15 days. The results showed that the effectiveness of water hyacinth E. azurea was 87% able to reduce the concentration of Cr6+ 0.78 ppm to 0.1 ppm within 15 days, while E. crassipes and the combination of E. crassipes and E. azurea were 64%. The rate of water hyacinth damage to Cr6+ wastewater was faster in E. azurea, namely 40% compared to E. crassipes by 27% and the combination of E. crassipes and E. azurea by 13%. The growth of water hyacinth in Cr6+ wastewater was faster in the combination of E. Crassipes and E. azurea, namely plant weight 45%, root length 38%, plant height 23% compared to E. azurea, namely plant weight 35%, root length 32%, height plant 17%, and E. crassipes, namely plant weight 45%, root length 38%, plant height 7%.